Discourse on Legal Expression in Arrangements of Corruption Eradication in Indonesia - Hidayat, Shubhan Noor; Karjoko, Lego; Hermawan, Sapto (Universitas Negeri Semarang, 2020)
The purpose of this research is to explain and examine the expansion of the absolute competence of the Administrative Court (hereinafter referred to as PTUN) after the Government Administration Law is promulgated and the implications of the application of the Administrative Law on legal certainty to eradicate and enforce corruption in Indonesia. This research uses a normative juridical research method and uses a statutory approach (statute approach). The results showed